E-Learning in Modern Education: Journey, Implementation, Challenges, and Future Potential - Didik Himmawan; Azizah Srie Nurningsih (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The development of digital technology has forced a transformation in the education system, where institutions are challenged to utilize new media to eliminate the barriers of space and time. This phenomenon has driven the rapid evolution of e-learning, from its initial CD-ROM-based approach to integration with Learning Management Systems (LMS) in the early 2000s, as well as content enrichment through multimedia and gamification to increase student engagement. However, this implementation faces significant challenges related to infrastructure requirements and individual technological adaptation. This study aims to analyze and describe the development of e-learning, compare implementations at the school and higher education levels, and evaluate its operational strengths and weaknesses, including the contribution of strategic thinking to e-learning optimization. This study uses a qualitative approach with a descriptive-analytical type and is based on literature review (document review) and conceptual analysis. Data are classified to analyze historical developments, compare implementations, and analyze benefits and challenges. Data analysis techniques include content and comparative analysis to draw relevant conclusions. The results of this study found that e-learning implementations have similarities in flexibility in access and use of technology, but differ in demands for independent learning and depth of material. Higher education emphasizes independence and more complex material, while schools are more structured. Furthermore, the quiz method has been proven to increase motivation and evaluation efficiency, but is hampered by internet access issues and a lack of direct interaction. E-learning is key to educational transformation that successfully increases accessibility and efficiency. Successfully optimizing e-learning requires a strategic approach, including developing effective platforms and enhancing lecturer capabilities, to overcome infrastructure limitations and challenges of direct interaction.